2016
DOI: 10.1111/nph.14274
|View full text |Cite
|
Sign up to set email alerts
|

Plant volatile‐mediated signalling and its application in agriculture: successes and challenges

Abstract: SummaryThe mediation of volatile secondary metabolites in signalling between plants and other organisms has long been seen as presenting opportunities for sustainable crop protection. Initially, exploitation of interactions between plants and other organisms, particularly insect pests, foundered because of difficulties in delivering, sustainably, the signal systems for crop protection. We now have mounting and, in some cases, clear practical evidence for successful delivery by companion cropping or next-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 139 publications
(205 reference statements)
2
146
0
Order By: Relevance
“…The components of the system need to be compatible with each other (Smart et al 1997) and while individually they can be relatively ineffective compared to the use of broad-spectrum insecticides, together they can have an additive or synergistic effect (Campbell and Borden 2009). The combination of relatively weak control elements has the added advantage of not selecting strongly for resistance in the pest species Pickett and Khan 2016).…”
Section: The Push-pull Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the system need to be compatible with each other (Smart et al 1997) and while individually they can be relatively ineffective compared to the use of broad-spectrum insecticides, together they can have an additive or synergistic effect (Campbell and Borden 2009). The combination of relatively weak control elements has the added advantage of not selecting strongly for resistance in the pest species Pickett and Khan 2016).…”
Section: The Push-pull Systemmentioning
confidence: 99%
“…Attack from herbivores is known to induce natural plant defence systems (Pickett and Poppy 2001;Howe and Jander 2008); therefore, crop plants themselves could act as the source of manipulative semiochemicals, using inducing agents, or natural product plant activators, to 'switch on' plant defence prior to attack (Pickett et al 2006). This alternative approach to genetic modification uses gene promoter systems that could create a self-protecting crop where primed sentinel crop plants use volatile signals to elicit faster defensive responses from the surrounding plants and natural enemies (Balmer et al 2015;Conrath et al 2015;Pickett and Khan 2016;Pickett 2016).…”
Section: Smart Self-protecting Cropsmentioning
confidence: 99%
“…Some plant species constitutively release volatile semiochemicals that repel insect pests and attract natural enemies of the herbivore [29,30]. More examples on ecological functions of plant-derived volatile semiochemicals have been well documented [9,23,31,32].…”
Section: Role Of Induced and Constitutive Volatiles In Plant Defencementioning
confidence: 99%
“…The HIPVs could be involved in direct resistance by acting as feeding and/or oviposition deterrents to insect pests [8,24] and provide protection against pathogens [25]. Indirectly, they mediate above-and below-ground interactions that attract herbivores' natural enemies [6,9] and serve as signals to neighbouring plants [26]. Our recent study on a wide range of maize germplasm revealed some maize genotypes emit HIPVs attractive to egg and larval parasitic wasps at the egg-laying stage of insect attack [27,28].…”
Section: Role Of Induced and Constitutive Volatiles In Plant Defencementioning
confidence: 99%
See 1 more Smart Citation